A Prospective Study of Differential Sources of School‐Related Social Support and Adolescent Global Life Satisfaction. (18th January 2013) - Siddall, James; Huebner, E. Scott; Jiang, Xu
<x xml:space="preserve">Abstract</x> This study examined the cross‐sectional and prospective relationships between three sources of school‐related social support (parent involvement, peer support for learning, and teacher‐student relationships) and early adolescents' global life satisfaction. The participants were 597 middle school students from 1 large school in the southeastern United States who completed measures of school social climate and life satisfaction on 2 occasions, 5 months apart. The results revealed that school‐related experiences in terms of social support for learning contributed substantial amounts of variance to individual differences in adolescents' satisfaction with their lives as a whole. Cross‐sectional multiple regression analyses of the differential contributions of the sources of support demonstrated that family and peer support for learning contributed statistically significant, unique variance to global life satisfaction reports. Prospective multiple regression analyses demonstrated that only family support for learning continued to contribute statistically significant, unique variance to the global life satisfaction reports at Time 2. The results suggest that school‐related experiences, especially family‐school interactions, spill over into adolescents' overall evaluations of their lives at a time when direct parental involvement in schooling and adolescents' global life satisfaction are generally declining. Recommendations for future research and educational policies and practices are discussed.